Penghitungan Waktu Standard Pelaksanaan Inspeksi Phase 1 Pesawat Beechcraft King Air B 200 di Balai Besar Kalibrasi Fasilitas Penerbangan - Kurniawan, Reja; Esthi Riyanti, Lilies; Herwanto, Djoko (Politeknik Penerbangan Makassar, 2021)
The research was conducted at Hangar C Balai Besar Kalibrasi Fasilitas Penerbangan. The research object was the standard time of the phase 1 inspection King Air B 200 series aircraft. The research used the stopwatch time study method with the Westinghouse rating instrument and the addition of allowance factors. Based on the research conducted, it was obtained the highest average data, the value was at the outboard wing section with the average time 1057.5 minutes and the lowest average time was at the operational check section with the average time 30 minutes. Futhermore, the average time data from observations using the Westinghouse rating method was processed then the normal time was found for each section of the process. By observing the adjustment factor (p) of the Westinghouse method, the highest normal time was gained at the outboard wing section, it was 1194.97 minutes and the lowest time at the operational check section was 33.9 minutes. After conducting the observations at hangar C, Balai Besar Kalibrasi Fasilitas Penerbangan (BBKFP) for the phase 1 inspection King Air B200 aircraft, it was obtained the allowance for each section of task card phase 1 inspection. The largest allowance value was at the engine cowling area and cabin section, it was 40.50% while the smallest allowance value was at the rear fuselage and empenage section, it was 22.50%. In order to get the standard time of the phase I inspection, it can be described from the normal time of each section on phase 1 inspection and the addition of the adjustment factor (p) and allowance. In addition, to get the total standard time of phase 1 inspection, it can be obtained by adding the standard time of each section. The total standard time of the inspection phase 1 was 6208.661 minutes or 103.5 hours.